Academic Library as the Space for the Development of Future Specialists’ Competence - Kardeliene Laimute; Kardelis Kęstutis; Bakutyte Rima (Discourse and Communication for Sustainable Education, 2014)
The article discloses the value of academic library. This value is deriving from the university purpose to prepare students to be able to deal with the increasing the flow of information in the society (Owusu - Ansah, 2001). Research was carried out in Utena University of applied science. First-year students (n = 140) made 48,3% of the sample, and third-year students (n = 150) - 51,7% of the investigated sample; males - 33,8% (n=98), and females - 66,2% (n=192). The conditions of academic library as student and future specialist empowered environment are validated: communicational, physical, pragmatic. The interpretation of research data disclosed that the academic library as learning environment and as environment which is empower the student to a professional qualification less or more improve future specialist professional, academically and as a personality. The future development of specialist competence effectiveness criteria can be considered as the nature of those experiences, which causes him to preparation for examinations and various settlements, preparation of projects and the search for the global academic community material created a topic of interest. The nature of experiences can reduce the educational impact of library. While improving learning environments are necessary to guide students with higher academic achievement and those who are spending more time in the library view.